The Impact Of Academic Supervision And Work Motivation On The Long-Term Development Of Teacher Professionalism In Elementary Education - Rizki Kurnia Dewi; Nurkolis Nurkolis; Ngurah Ayu Nyoman Murniati (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study aims to analyze the impact of academic supervision and work motivation on the long-term development of teacher professionalism in elementary education. Using a quantitative approach with a survey method, the study population consisted of elementary school teachers in Purwodadi District, Grobogan, Central Java, Indonesia, with a sample of 220 teachers selected through proportional random sampling. Data were collected using a questionnaire that had been tested for validity and reliability. Data analysis was conducted using Pearson correlation and linear regression to examine the effect of each variable on teacher professionalism. The results show that academic supervision has a positive and significant relationship with teacher professionalism (correlation coefficient of 0.512 and contribution of 26.2%), while work motivation also has a positive and significant relationship (correlation coefficient of 0.407 and contribution of 16.6%). These findings indicate that improving the quality of academic supervision conducted by school principals and strengthening teachers' work motivation play an essential role in enhancing teacher professionalism. This study provides empirical insights that can be used to develop strategies for the sustainable improvement of teacher professionalism. However, the study has limitations related to variables not explored, and further research is suggested to include additional external factors that may affect teacher professionalism.